PENGARUH KEPEMIMPINAN KEPALA SEKOLAH, KOMPETENSI DIGITAL DAN KEPUASAN KERJA TERHADAP KINERJA GURU MELAKSANAKAN KURIKULUM MERDEKA - Fitriani, Ida; A Gani, Muzakkar; Dewi, Silvi Listia (Hijri, 2024)
The purpose of this research is (1) to determine the influence of the principal's leadership on teacher performance in implementing the Merdeka Curriculum in elementary schools in Johan Pahlawan District, West Aceh Regency. (2) To determine the influence of digital competence on teacher performance in implementing the Independent Curriculum in elementary schools in Johan Pahlawan District, West Aceh Regency. (3) To determine the effect of job satisfaction on teacher performance in implementing the Independent Curriculum in elementary schools in Johan Pahlawan District, West Aceh Regency. The type of research is quantitative research using a research sample of 80 elementary school teachers in Johan Pahlawan District, the sampling technique is stratified random sampling. Likert scale questionnaire data collection techniques and data processing techniques for multiple linear regression analysis. Partial research findings obtained (1) the principal's leadership influences the performance of elementary school teachers with a significant value of 0.000. (2) digital competence influences the performance of elementary school teachers with a significant value of 0.002. (3) teacher satisfaction influences elementary school teacher performance with a significant value of 0.006. Research findings simultaneously show that school principal leadership, digital competence and job satisfaction simultaneously influence the performance of elementary school teachers implementing the independent curriculum in Johan Pahlawan District, West Aceh Regency with a significant value of 0.0000. From the results of this research, it can be concluded that the principal's leadership, digital competence and job satisfaction influence the performance of elementary school teachers implementing the independent curriculum in Johan Pahlawan District, West Aceh Regency